2016
DOI: 10.1016/j.rbmo.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian function during hormonal contraception assessed by endocrine and sonographic markers: a systematic review

Abstract: This systematic review focuses on the literature evidence for residual ovarian function during treatment with hormonal contraceptives. We reviewed all papers which assessed residual ovarian activity during hormonal contraceptive use, using endocrine markers such as serum anti-Müllerian hormone (AMH) concentrations, FSH, LH, oestradiol, progesterone and sonographic markers such as antral follicle count (AFC), ovarian volume and vascular indices. We considered every type (oestroprogestin or only progestin) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 64 publications
(124 reference statements)
0
37
0
Order By: Relevance
“…Use of OC alters hormone levels, and this further depends on the type, dosage, and mode of administration of OC. It has been observed by others that FSH, LH, and estradiol serum concentration levels decrease during OC use (D'Arpe et al, ). Inconsistent results were reported in relation to anti‐Mullerian hormone (AMH) which is used as an ovarian aging marker and an indicator of a woman's ovarian reserve.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Use of OC alters hormone levels, and this further depends on the type, dosage, and mode of administration of OC. It has been observed by others that FSH, LH, and estradiol serum concentration levels decrease during OC use (D'Arpe et al, ). Inconsistent results were reported in relation to anti‐Mullerian hormone (AMH) which is used as an ovarian aging marker and an indicator of a woman's ovarian reserve.…”
Section: Discussionmentioning
confidence: 94%
“…Inconsistent results were reported in relation to anti‐Mullerian hormone (AMH) which is used as an ovarian aging marker and an indicator of a woman's ovarian reserve. While some studies observed that OC use did not influence AMH concentrations, other studies reported lower levels of AMH in OC users than in non‐users (D'Arpe et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Second, during the initial evaluation most of the patients were on hormonal treatment (80% were taking oral progestin). The effect of hormonal treatment on AMH level remains a matter of debate [29], but few studies suggest that progestin drugs tend to decrease AMH levels [30]. Third, we chose the number of retrieved and vitrified oocytes as outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…All descriptive and analytic results are stratified according to the use of hormonal contraceptives by the participants. Serum concentrations of FSH, LH, DHEAS, and E 2 in hormonal contraceptive users are reported for information only, given their suppression during hormonal contraceptive treatment (10).…”
Section: Discussionmentioning
confidence: 99%